Quantification of persister formation of Escherichia coli leveraging electronic cell counting and semi-mechanistic pharmacokinetic/pharmacodynamic modelling. (17th May 2021) - Seeger, Johanna; Michelet, Robin; Kloft, Charlotte
Abstract: Background: Persister formation of Escherichia coli under fluoroquinolone exposure causes treatment failure and promotes emergence of resistant strains. Semi-mechanistic pharmacokinetic/pharmacodynamic modelling of data obtained from in vitro infection model experiments comprehensively characterizes exposure–effect relationships, providing mechanistic insights. Objectives: To quantify persister formation of E. coli under levofloxacin exposure and to explain the observed growth-kill behaviour, leveraging electronic cell counting and pharmacokinetic/pharmacodynamic modelling. Methods: Three fluoroquinolone-resistant clinical E. coli isolates were exposed to levofloxacin in static and dynamic in vitro infection model experiments. Complementary to plate counting, bacterial concentrations over time were quantified by electronic cell counting and amalgamated in a semi-mechanistic pharmacokinetic/pharmacodynamic model (1281 bacterial and 394 levofloxacin observations). Results: Bacterial regrowth was observed under exposure to clinically relevant dosing regimens in the dynamic in vitro infection model. Electronic cell counting facilitated identification of three bacterial subpopulations: persisters, viable cells and dead cells. Two strain-specific manifestations of the levofloxacin effect were identified: a killing effect, characterized as a sigmoidal Emax model, and an additive increase in persister formation under levofloxacin exposure. Significantly different EC50 values quantitatively discerned levofloxacin potency for two isolates displaying the same MIC value: 8 mg/L [EC50  = 17.2 (95% CI = 12.6–23.8) mg/L and 8.46 (95% CI = 6.86–10.3) mg/L, respectively]. Persister formation was most pronounced for the isolate with the lowest MIC value (2 mg/L). Conclusions: The developed pharmacokinetic/pharmacodynamic model adequately characterized growth-kill behaviour of three E. coli isolates and unveiled strain-specific levofloxacin potencies and persister formation. The mimicked dosing regimens did not eradicate the resistant isolates and enhanced persister formation to a strain-specific extent.